Trade finance gaps, growth, and jobs survey. - DiCaprio, Alisa (Metro Manila, Philippines Asian Development Bank, 2017)
This brief discusses the 2017 ADB Trade Finance Gaps, Growth, and Jobs Survey which quantifies global market gaps for trade finance and the impact on growth and jobs.
Keywords: Financial institutions -- Asia; Banks and banking -- Asia; Finance -- Government policy -- Asia; Electronic books